Reliability of the Clozapine:N-Desmethylclozapine (CLZ:NDMC) Ratio. Issue 1 (12th October 2021) - Solomon, Shirlee Daniela; Powell, Valerie; Sanches, Marcos; Borlido, Carol; Burton, Leah; De Luca, Vincenzo; Rajji, Tarek; Remington, Gary
Abstract: Clozapine represents the only agent approved for treatment resistant schizophrenia (TRS). Clear dosing guidelines have been difficult to delineate, and therapeutic drug monitoring (TDM) has become a common method to guide clinical use. In this context, attention has also focused on the ratio between clozapine (CLZ) and its metabolite, N -desmethylclozapine (NDMC). The CLZ:NDMC ratio has been implicated in cognition, an important clinical domain in schizophrenia, and various clinico-demographic factors are thought to impact it. To date, the reliability of the CLZ:NDMC ratio has not been established, and the present study aimed to (i) calculate the intraclass correlation coefficient (ICC) for the CLZ:NDMC ratio to assess reliability, and (ii) investigate the effect of selected clinico-demographic factors. The sample consisted of 100 patients diagnosed with schizophrenia or schizoaffective disorder being treated with clozapine, stabilized on their current dose, and able to provide at least 2 TDM samples. The calculated ICC for the CLZ:NDMC ratio was 0.65, while sex and co-administration of a mood stabilizer, specifically divalproex sodium, were found to significantly impact the ratio. In conclusion, the CLZ:NDMC ratio is moderately reliable, and can be influenced by clinical variables that warrant further investigation. Key limitations of the present investigation include inability to collect data on relevant variables such as smoking and ethnicity, as well as categorical exclusion of known inhibitors/inducers of clozapine metabolism. At the same time, these limitations underscore the challenges in utilizing such measures in clinical practice.